OPTIMIZATION IN UNIVERSITY GRADUATES STRUCTURE ORIENTED TO THE LABOR MARKET: MINIMAX APPROACH - Shorikov, A.F.; Sudakova, A.Ye. (Perm Federal Research Centre Journal, 2016)
The article discusses the problem of optimizing the product mix of specialists with university orientation to the labor market. The solution to this problem lies in the minimax approach that is supposed to form the phase vector of the system and the vector control action (control), which enables to influence the structure, quantity and quality of graduates in various educational programs. Optimization model construction for this problem is supposed to implement in two stages.